(untitled) - Kardolus, Jouke Pieter (Netherlands, 1998)
This thesis describes a biosystematic analysis of the allotetraploid species Solanum acaule. Solanum acaule is one of the circa 200 tuber-bearing Solanum species (Solanum sect. Petota, Solanaceae) and often used in plant breeding programs for its disease resistances and frost tolerance.
Keywords: Biosystematics,Solanum acaule,Sinh học hệ thống